Rancang Bangun Module Media Pembelajaran Bentuk Aljabar Berbasis Mobile - Abdul Ghofur; Harun Mukhtar; Evans Fuad (Jurnal CoSciTech (Computer Science and Information Technology), 2020)
Algebra is one branch of mathematics that studies simplification and problem solving using symbols that are substitutes for constants or variables. Algebra in middle school children is usually obtained in class VII where the learning process uses textbooks and practices are simple. On the other hand, as more and more interactive learning media emerge that teach children, then with these considerations, the authors took the initiative to build a Mobile-Based Algebra Form Learning Media Design that can help the learning process more interesting.